A case of cowpox virus infection in a 15-year-old boy and literature overview - Wiącek, Katarzyna; Cwynar, Justyna; Bursa, Dominik; Horban, Andrzej; Telega, Grzegorz; Mazur, Artur (Pediatria Polska - Polish Journal of Paediatrics, 2017)
We describe a 15-year-old boy who presented with multiple ulcerative lesions of the face. Cowpox virus infection was diagnosed by polymerase chain reaction (PCR) and high titers of serum Orthopoxvirus-specific IgM and IgG antibodies. Healing with significant scarring and lagophthalmos of the left eye occurred.